The Influence of E-Recovery Service Quality and E-Service Quality on Loyalty through Tokopedia Customer Satisfaction - Ike Puspitayanti; Sunarno; Mochamad Edris (Journal of Finance and Business Digital, 2023)
Based on the results of the analysis and discussion, the conclusions in this research are as follows: (1) E-Recovery Service Quality has a positive and significant effect on customer satisfaction at the Tokopedia Marketplace; (2) E-Service Quality has a positive and significant effect on customer satisfaction at the Tokopedia Marketplace (3) E-Recovery Service Quality has a positive and significant effect on customer loyalty at the Tokopedia Marketplace; (4) E-Service Quality has a positive and significant effect on customer loyalty to the Tokopedia Marketplace: (5) Customer satisfaction has a positive and significant effect on customer loyalty to the Tokopedia Marketplace.